2022
DOI: 10.3390/fermentation8080396
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrogen and Methane Production from Sugarcane Leaves Pretreated by Deep Eutectic Solvents and Enzymatic Hydrolysis by Cellulolytic Consortia

Abstract: This study determined the optimal conditions for the deep eutectic solvent (DES) pretreatment of sugarcane leaves and the best fermentation mode for hydrogen and methane production from DES-pretreated sugarcane leaves. Choline chloride (ChCl):monoethanolamine (MEA) is the most effective solvent for removing lignin from sugarcane leaves. The optimum conditions were a ChCl: MEA molar ratio of 1:6, 120 °C, 3 h, and substrate-to-DES solution ratio of 1:12. Under these conditions, 86.37 ± 0.36% lignin removal and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
4
5
0
Order By: Relevance
“…The hydrogen yields obtained in our study are similar to those reported by other authors from lignocellulosic substrates [25,29]. Miftah et al [29] reported hydrogen yields of 0.8 to 39.8 mL H 2 /g from pretreated and non-pretreated sugarcane leaves.…”
Section: Conflicts Of Interestsupporting
confidence: 91%
See 3 more Smart Citations
“…The hydrogen yields obtained in our study are similar to those reported by other authors from lignocellulosic substrates [25,29]. Miftah et al [29] reported hydrogen yields of 0.8 to 39.8 mL H 2 /g from pretreated and non-pretreated sugarcane leaves.…”
Section: Conflicts Of Interestsupporting
confidence: 91%
“…The hydrogen yields obtained in our study are similar to those reported by other authors from lignocellulosic substrates [25,29]. Miftah et al [29] reported hydrogen yields of 0.8 to 39.8 mL H 2 /g from pretreated and non-pretreated sugarcane leaves. Perez-Rangel et al [25] obtained 13, 17, and 38 mL H 2 /g VS from agave bagasse, corn stalk, and wheat straw, respectively.…”
Section: Conflicts Of Interestsupporting
confidence: 91%
See 2 more Smart Citations
“…Aseptically, a 10 % (v/v) solution of KKU-MC1 was injected into each bottle. The bottles were then incubated at 37 °C and 150 rpm for 5 days [ 11 , 23 ]. The control test followed the same procedure, but without the addition of KKU-MC1.…”
Section: Methodsmentioning
confidence: 99%